Społeczna rola intelektualisty-nauczyciela akademickiego - refleksje = A social role of an intellectual - an academic teacher - afterthoughts - Kowalski, Mirosław; Kowalska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article concerning the contemporary role (roles) of academic teachers we undertake an attempt to answer the following questions: What is the humanistic tradition of "being an expert", "being a counsellor"?; Who is a thinker, an intellectual according to the humanistic tradition?; Are the requirements towards an expert, counsellor on one hand and a thinker, intellectual on the other hand to be met, in other words?; May a scientist-humanist effectively play these two roles?
Keywords: nauczyciel akademicki